172k views
3 votes
Solve. 6-6x = 6x - 8x + 18​

User Spydon
by
4.8k points

2 Answers

2 votes

Answer:

6-6x=-8x-18

We move all terms to the left:

6-6x-(-8x-18)=0

We get rid of parentheses

-6x+8x+18+6=0

We add all the numbers together, and all the variables

2x+24=0

We move all terms containing x to the left, all other terms to the right

2x=-24

x=-24/2

x=-12

Explanation:

hope this helps!! :D

User Gruvw
by
4.7k points
3 votes

Answer:

x=-3 that will be ur answer

User Rodrigo Zurek
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.